Cloning of the Gene Encoding the Actinobacillus actinomycetemcomitans Serotype b OmpA-Like Outer Membrane Protein - Komatsuzawa, Hitoshi (American Society for Microbiology, 1999)
The gene encoding an outer membrane protein A (OmpA)-like, heat-modifiable Omp of Actinobacillus actinomycetemcomitans ATCC 43718 (strain Y4, serotype b) was cloned by a PCR cloning procedure. DNA sequence analysis revealed that the gene encodes a protein of 346 amino acid residues with a molecular mass of 36.9 kDa. The protein expressed by the cloned gene reacted with a monoclonal antibody to the previously described 29-kDa Omp (Omp29) of strain Y4. This monoclonal antibody reacted specifically with Omp29 of A. actinomycetemcomitans (serotype b), but not with any Omp of Escherichia coli, including OmpA. This protein exhibited characteristic heat modifiability on sodium dodecyl sulfate-polyacrylamide gels, showing an apparent molecular mass of 29 kDa when unheated and a mass of 34 kDa when heated. The N-terminal amino acid sequence of the protein expressed in E. coli perfectly matched those deduced from the purified Omp29 of strain Y4. The deduced amino acid sequence of the gene coding for Omp29 from serotype b matched completely (except for valine at position 321) that of a recently reported omp34 gene described for A. actinomycetemcomitans serotype c (NCTC 9710). Because of the conserved nature of the gene within these serotypes, we designated the gene described herein from serotype b as omp34.